2019
DOI: 10.3390/ijerph16214071
|View full text |Cite
|
Sign up to set email alerts
|

Acute Febrile Illness Caused by Brucella Abortus Infection in Humans in Pakistan

Abstract: Brucellosis is a zoonosis of great and worldwide public health concern that can cause a severe febrile illness in humans. In Pakistan, brucellosis is a critical problem in both animals and humans. This study aimed to gain insight into its prevalence and to analyze the potential risk factors of patients with acute febrile illness (AFI) of an unknown cause, at the hospitals of Rawalpindi and Islamabad in Pakistan. In total, 446 blood samples were collected from patients and screened for brucellosis using the Ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
(64 reference statements)
5
15
0
Order By: Relevance
“…Brucella abortus DNA was detected in sera from 13 cattle and 18 buffalo cows. This current finding agrees with previous reports indicating the endemicity of B. abortus in bovines in Pakistan ( 17 , 21 , 32 , 34 – 36 ). One study also reported Brucella melitensis infection in bovines ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Brucella abortus DNA was detected in sera from 13 cattle and 18 buffalo cows. This current finding agrees with previous reports indicating the endemicity of B. abortus in bovines in Pakistan ( 17 , 21 , 32 , 34 – 36 ). One study also reported Brucella melitensis infection in bovines ( 12 ).…”
Section: Discussionsupporting
confidence: 93%
“…Brucellosis is endemic in many countries in Africa, Middle East, Mediterranean Basin, Asia, and Latin America with high records in humans in the Middle East and central Asian regions ( 16 ). It is endemic in Pakistan where it affects various livestock species and humans ( 12 , 17 ). Disease burden particularly in bovines is increasing due to commercialization, urbanization, and increasing trends of extensive livestock farming ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis remains a persistent zoonotic infection mainly caused by B. abortus and B. melitensis in ruminants in Pakistan and neighboring countries [25][26][27][28][29][30][31][32][33]. Canine brucellosis (B. canis) has also been reported in surrounding countries [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, the incidence of brucellosis is increasing day by day due to a lack of awareness [ 13 ]. Few studies concerning human brucellosis in Pakistan have been carried out in the last decade [ 14 , 15 , 16 , 17 , 18 ]. The present study aims to determine the seroprevalence of brucellosis and molecular detection of Brucella spp.…”
Section: Introductionmentioning
confidence: 99%